Pengaruh Kompos dari Berbagai Bagian Eceng Gondok terhadap Pertumbuhan dan Hasil Tanaman Seledri - Sam’ah Sam’ah; Mahdiannoor Mahdiannoor; Norhasanah Norhasanah (Rawa Sains: Jurnal Sains STIPER Amuntai, 2013)
Celery plants like planting media that have lots of water but are not flooded. Water hyacinth grows on swamps and has the potential to be a source of organic fertilizer. The successful use of water hyacinth as compost material will provide multiple benefits. Besides being able to obtain compost which can restore soil fertility, it can also reduce losses caused by water hyacinth. This study aims to (i) determine the effect of compost from various parts of water hyacinth on the growth and yield of celery plants, (ii) obtain the best parts of various parts of water hyacinth compost on the growth and yield of celery plants. The study was carried out in the Danau Panggang Village of Danau Panggang Subdistrict in March 2012 to May 2012, this study used Randomized block design (RBD) with one factor. The treatments that were tried were compost from various parts of water hyacinth (E) which consisted of 4 levels, namely: control e0 (without treatment), e1: bottom compost (root,) e2: upper compost (stem and root), and e3: compost all parts of the plant. The results of this study showed that the compost from the water hyacinth root (e1) was the best treatment for the observation of plant height, leaf number and wet weight of celery plants.